Challenges in the Implementation of the Bologna Process: Focusing on Three Universities of Kurdistan Region of Iraq - Jabbar H. Ade (Polytechnic Journal)
Bologna process is the instruction for reshaping in the higher education system, which created significant obstacles for its implementation. The objective of this study is to investigate the issues and challenges faced Kurdistan universities during the implementation of the Bologna process. In this study, three universities have been focused; two public and a private university. A questionnaire form was designed or the three universities’ staff (Erbil Polytechnic University [EPU], Soran University, and Cihan University) which included several questions about the challenges faced them during European Credit Transfer System (ECTS) implementation. The results show that Cihan University provides more knowledge about Bologna process to its staff while EPU and Cihan University were the best regarding staff participation in Bologna process and related events such as conferences, workshops, and seminars. EPU shows to be preferable in providing ECTS instructions While Cihan University tends to be better followed the policy of ECTS. Most Universities’ staff disagreed about the success of the Bologna process implementation due to unsuitable universities’ infrastructure and academic calendar. In conclusion, in point of view of the universities’ staff, several steps have been taken toward the implementation of Bologna process, but it required more preparations and efforts.